Polar and antipolar polymorphs of metastable perovskite BiFe0.5Sc0.5O3 - Khalyavin, D. D. (2017)
A metastable perovskite BiFe0.5Sc0.5O3 synthesized under high-pressure (6 GPa) and high-temperature (1500 K) conditions was obtained in two different polymorphs, antipolar Pnma and polar Ima2, through an irreversible behavior under a heating/cooling thermal cycling. The Ima2 phase represents an original type of a canted ferroelectric structure where Bi3+ cations exhibit both polar and antipolar displacements along the orthogonal [110](p) and [1 (1) over bar0](p) pseudocubic directions, respectively, and are combined with antiphase octahedral tilting about the polar axis. Both the Pnma and the Ima2 structural modifications exhibit a long-range antiferromagnetic ordering with a weak ferromagnetic component below T-N similar to 220 K. Analysis of the coupling between the dipole, magnetic, and elastic order parameters based on a general phenomenological approach revealed that the weak ferromagnetism in both phases is mainly caused by the presence of the antiphase octahedral tilting whose axial nature directly represents the relevant part of Dzyaloshinskii vector. The magnetoelectric contribution to the spontaneous magnetization allowed in the polar Ima2 phase is described by a fifth-degree free-energy invariant and is expected to be small.